Simultaneous Estimation of Metronidazole and Ofloxacin in Suspension Dosage Form Using UV-Visible Spectrophotometer - Lalhriatpuii, T.C.; K. Jatav, Rakesh; K. Goel, Pradeep; Kawathekar, N. (Asian Journal of Chemistry, 2010)
Four accurate, sensitive and economical procedures for simultaneous estimation of metronidazole and Ofloxacin in suspension dosage form have been developed. The methods employed are Simultaneous equation method; first order derivative method, two wavelengths method and graphics absorbance ratio method for the simultaneous estimation of metronidazole and ofloxacin. The first method employs the formation and solving of simultaneous equations using 324.8 nm and 301.4 nm as the two wavelengths for forming equations. The second method employs first order derivative spectroscopy to eliminate spectral interference. The third method employs 324.8 nm and 282.8 nm as λ1 and λ2 and 301.0 nm and 344.8 nm as λ1 and λ2 for metronidazole and ofloxacin respectively. The fourth method employed 266.0 nm as A1 (isobestic point) and 324.5 nm as A2 that is the λmax of metronidazole. Both drugs obey Beer's law in the concentration ranges employed for the analysis. The results of analysis have been validated statistically and by recovery studies.